2006
DOI: 10.1007/s00467-006-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-glycoprotein in lymphocytes from children with nephrotic syndrome, depending on their steroid response

Abstract: The aim of this study was to examine the expression of P-glycoprotein (P-gp) in CD3 lymphocytes of children with nephrotic syndrome (NS) in relation to their clinical response to glucocorticoid (GC) treatment. The examinations were performed on two groups. The study group (I) consisted of 88 children aged 2.0-20.0 years with NS, divided according to their clinical response to GC: NFR-non-frequent relapse NS; FR-frequent relapse NS; SD-steroid-dependent NS. The control group (II) consisted of 18 healthy childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…[9] In addition, expression of MDR1 and P-gp activity are negatively correlated with steroid sensitivity in children with NS. [10–12] Furthermore, there is evidence that polymorphisms in MDR1 may influence disease occurrence and response to drug treatment through changes in gene expression and P-gp activity. [13] …”
Section: Introductionmentioning
confidence: 99%
“…[9] In addition, expression of MDR1 and P-gp activity are negatively correlated with steroid sensitivity in children with NS. [10–12] Furthermore, there is evidence that polymorphisms in MDR1 may influence disease occurrence and response to drug treatment through changes in gene expression and P-gp activity. [13] …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the association of P-gp expression with the responsiveness to steroids in patients with idiopathic NS [36][37][38]. Wasilewska et al [38] measured P-gp expression on CD3-positive lymphocytes and found that CD3/P-gp expression was significantly higher in patients with NS than in the controls and that the difference was higher in steroid-dependent and frequent relapsing groups than in the non-frequent relapsing group. Funaki et al [36] reported that the MDR1 mRNA expression level in nucleated cells of peripheral blood was variable in patients with idiopathic NS prior to remission, but apparently decreased after complete remission.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of structurally unrelated drugs, including steroids, are known to be substrates for P-gp [34,35]. Several studies have been conducted to evaluate the association of P-gp expression with the responsiveness to steroids in patients with idiopathic NS [36][37][38]. Wasilewska et al [38] measured P-gp expression on CD3-positive lymphocytes and found that CD3/P-gp expression was significantly higher in patients with NS than in the controls and that the difference was higher in steroid-dependent and frequent relapsing groups than in the non-frequent relapsing group.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of P-glycoprotein results in decreased intracellular drug concentrations and may consequently decrease treatment response. Previous research has shown higher expression of MDR1 and increased P-glycoprotein activity in children with steroid-resistant nephrotic syndrome [116,117]. To date, approximately 50 genetic polymorphisms have been reported in the MDR1 gene.…”
Section: Glcci1 (Glucocorticoid-induced Transcript 1 Gene)mentioning
confidence: 99%